Humanisasi Pendidikan dalam Pembentukan Kesadaran Keberagaman Umat Lintas Agama di Lamongan - Abidin, Upik Khoirul (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2016)
The discourse of interreligious harmony and tolerance has been widely discussed within countless forums. However, the phenomenon of religious disharmony, which is among other marked with social clashes, has been erroneously manipulated into intergroup conflicts among interreligious adherents. Such interreligious disharmony, viewing from simplistic category, has been commonly caused by two factors. The first is an internal factor, i.e. the factor which influences a person to behave based on his/her understanding to religious doctrines he/she subscribes such as radical-extreme, subjective-fundamental, exclusive, and literal behaviors. The second is an external factor, i.e. hedonistic and opportunistic behaviors. The article seeks to discuss interreligious harmony in the Village of Balun, Turi, Lamongan. The village is a home to three different religions, namely Islam, Christianity, and Hinduism. Regardless of such difference the Balun people have successfully created harmony among them. The study finds that there has been sort of values transformation of humanism education in the village. The values such as human rights, tolerance, solidarity, familial relationship, and social justice are culturally transformed through what so-called the Forum of Solidarity for Balun People (Forum Keakraban Warga Balun/FKWB).